(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article briefly looks through the measures and Presidential Decrees, which were assigned to improve the quality and services rendered. Since independence, Uzbekistan faced the challenges of maintaining the supply of drugs and vaccines, while developing and implementing its own national drug policy. The gradual development of a national drug policy resulted in a clear division of the roles of the government and private sector. The government maintained mostly regulatory functions, while production and distribution were delegated to the private sector.